Integrative revision of Dianthus superbus subspecies reveals different degrees of differentiation, from plasticity to species distinction. Issue 3 (2nd April 2020) - Hardion, Laurent; Perrier, Antoine; Martinez, Marion; Navrot, Nicolas; Gaquerel, Emmanuel; Tournay, Frédéric; Nguefack, Julie; Combroux, Isabelle
Abstract : Within many species, confusions occur between infraspecific taxa, recurrent ecotypic differentiation and phenotypic plasticity. Subspecies are often debated when they are supported only by slight morphological differentiation coupled to habitat variation. In this context we tested the evolutionary support of the four contested subspecies of Dianthus superbus . Based on 147 Eurasian accessions, our integrative study combines three complementary approaches: (i) Genetic differentiation, with neutral genetic markers, i.e. 326 AFLP markers, 25 nuclear microsatellites and nrDNA ITS ribotypes; (ii) morphological differentiation, with 20 morphometric characters measured in situ and ex situ to assess phenotypic variation; (iii) ecological differentiation, indirectly based on 128 floral volatile compounds under selection of habitat-specific pollinators. Phylogenetic, morphometric and biochemical analyses support the distinction between European and East Asian samples, with an intermediate position of Central Asian samples. However, in Europe, phylogenetic markers only slightly distinguish West from Central European samples, without support for subspecies. Morphometric differentiation was found for subsp. alpestris . This morphotype was stable ex situ under different climatic conditions, and also supported by slight differences in volatile scents and phenology. Infraspecific taxonomy still reveals interesting polymorphisms, but also calls for a revision toward refined taxa. Dianthus superbus subspecies highlighted three dissimilar cases: (i) the East Asian subsp. longicalycinus must be considered as a distinct species; (ii) the morphometric and ecological distinction of subsp. alpestris supports its ecotypic differentiation despite a lack of phylogenetic divergence; (iii) subsp. sylvestris was not supported by any markers, arguing for an artefact of phenotypic plasticity under different environmental conditions.